Avaliação do fator de idade em concretos com distintas composições - Freitas, Maria Silva (2022)
The present work studied and determined the aging factor for concrete mixtures containing pozzolanic additions, considering measurements of electrical resistivity and diffusion of chloride ions in a laboratory environment. For this pourpose, cylindrical specimens with 100 mm diameter and 200 mm high were casted for eight different mixtures, composed of Portland cement of initial high strength, fly ash, metakaolin and silica fume. After the curing period, the samples were submitted to pure diffusion tests, following the recommendations of NT Build 443; surface electrical resistivity, by Wenner method; axial compressive strength and total water absorption by immersion. The results show that the age factor varied in a range of 0.100 to 0.999. For the age factor obtained from diffusion data, age factor "n", this interval was divided into three: 0.100 – 0.450, concrete without addition and concrete with the addition of silica fume; 0.300 - 0.600, concrete with the addition of metakaolin; 0.600 - 0.900, concrete with added fly ash. For the factor "q", an ageing factor obtained by readings of surface electrical resistivity, this interval ranged from: 0 - 0.420, for concrete without addition, concrete with the addition of silica fume and concrete with the addition of metakaolin, 0.620 - 0.999 for concrete with the addition of fly ash.